TINJAUAN YURIDIS PENUNJUKAN ANGGOTA TNI POLRI AKTIF SEBAGAI PELAKSANA TUGAS, PENGGANTI JABATAN KEPALA DAERAH DI INDONESIA - M. Zulfahmi; Emilda Firdaus; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The proposal to appoint the Indonesian National Police as an Acting(Pj) Regional Head by the Ministry of Home Affairs (Kemendagri) reapedpolemic. This is done to fill the position of regional head whose term of officeends before the election of a new regional head as a result of the Regional HeadElection (Pilkada). Rules regarding the appointment of Acting regional heads canbe found in Article 201 paragraph (10) of the Election Law which states: To fillthe vacancy in the position of Governor, an acting Governor is appointed from theposition of mid-high leadership up to the Governor's inauguration in accordancewith the provisions of laws and regulations.In addition, Article 4 paragraph (2) Permendagri Number 1 of 2018concerning Amendments to Minister of Home Affairs Regulation Number 74 of2016 concerning Leave outside the State's responsibility for Governors andDeputy Governors, Regents and Deputy Regents, as well as Mayors and DeputyMayors stipulate the Law Number 1 of 2015 concerning the Election ofGovernors, Regents and Mayors that Governor officials come from middle/highlevel leadership officials within the central/provincial government. Theappointment was carried out with the nuances of the upcoming regional headelection and allegedly having political content which not only has the aim ofmaintaining the publication and security of the implementation of regional headelections, but is suspected to be in the interest of winning one of the candidatepairs desired by those with an interest in this matter by rulers who come from theincumbents, therefore the author has the inclination and interest to analyze thisconstitutional issue in a thesis research so that a consensus can be obtained thathas a guarantee of juridical and scientific truth.Normative Juridical Research, namely an approach based on the mainlegal material by examining the theories, concepts, legal principles and statutoryregulations related to this research. This approach is also known as the libraryapproach, namely by studying books, laws and regulations and other documentsrelated to this research, library research, namely research conducted inreviewing, analyzing and formulating books, literature, and others that arerelevant to the title of this thesis.Keywords: Appointment of Police Officers - Acting Regional Head - State CivilApparatus